2012
DOI: 10.1002/art.34667
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone prodrug treatment prevents nephritis in lupus‐prone (NZB × NZW)F1 mice without causing systemic side effects

Abstract: Objective To evaluate the potentially improved therapeutic efficacy and safety of nephrotropic macromolecular prodrugs of glucocorticoids (GC) in the treatment of lupus nephritis. Methods Monthly injection of N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-based dexamethasone prodrug (P-Dex) and daily injection of dexamethasone phosphate sodium (Dex, overall dose equivalent to P-Dex) were given to lupus-prone (NZB×NZW)F1 female mice for two months. The animals were monitored for albuminuria, mean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…Results from studies of animal models of inflammatory diseases, including LN, have indicated that this dexamethasone formulation provides sustained resolution of inflammation [62, 63]. Studies have not yet been reported in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies of animal models of inflammatory diseases, including LN, have indicated that this dexamethasone formulation provides sustained resolution of inflammation [62, 63]. Studies have not yet been reported in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to address this problem, we have developed macromolecular prodrugs of anti-inflammatory agents, which passively target to inflammation. This approach is based on a mechanism involving the prodrug's e xtravasation through l eaky v asculature and i nflammatory cell-mediated s equestration (ELVIS) and has been validated in several inflammatory disease models [13, 14, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we employed a murine calvaria particle implant model and demonstrated the utility of the HPMA copolymer system to detect early particle-induced inflammation [13]. Though the murine calvaria osteolysis model reflects many biological features of the wear debris-associated osteolysis [10, 29], the lack of a prosthetic implant and a prosthesis/medullar canal interaction does not recapitulate the actual clinical setting associated with peri-implant osteolysis after total joint replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-CT scanning parameters were identical to those described previously [4]. Femoral BMD, BV/TV and trabecular number and thickness were quantified with CTAn software (Skyscan).…”
Section: Methodsmentioning
confidence: 99%